No-shows in ambulatory clinics and non-utilized appointments for elective operations in selected surgical departments at a tertiary hospital in Israel - Lior Cohen-Yatziv; Matan Joel Cohen; Jonathan Halevy; Ehud Kaliner (BMC, 2019)
Abstract Background The phenomenon of a patient missing a medical appointment without notification is called a "no-show". In contrast, "non-utilized appointments" are a broader phenomenon including all appointments that didn't occur as registered - whether due to actions taken by providers or patients. Both no-shows and non-utilized appointments can lead to reduced quality of care, loss in productivity, financial losses and impaired patient outcomes. Methods The study was carried out between August 2016 and January 2017 in the ENT, Orthopedics and General Surgery Departments of the Jerusalem-based Shaare Zedek Medical Center. The study team sought to examine the reasons for non-utilized appointments in elective operations. The study team also interviewed no-show ambulatory care patients regarding the causes of the no-show and reviewed medical records of no-show patients to determine the nature of the missed appointments. Results The rate of non-utilization of appointments for elective operations was 6%. The leading reasons for non-utilization of these appointments were: patient health issues, patient surgery postponement and surgery schedule overload (together accounting for 52% of cases and 72% of known reasons). The no-show rate for ambulatory clinic appointments was approximately 15%. The leading reasons for ambulatory clinic no-shows were: administrative issues, illness and forgetfulness (together accounting for 58% of all reasons). The leading types of appointments missed were:post-operation follow-ups and chronic illness follow-up (together accounting for 46% of cases and 63% of known reasons). Conclusions In this study, the non-utilized appointment rate for elective operations was found to be lower than those noted in the medical literature, while the no-show rate for ambulatory visits was found to be similar to that found in the literature. There is room to question the necessity of certain types of postoperative follow-up appointments since they are at "high risk" for no-show. One promising way to reduce the no-show rate would involve improving the hospital's information and computing systems in order to identify patients who are susceptible to a no-show incident.